The Children's dental health program - Widiya Ulfa (BKM Public Health and Community Medicine, 2021)
Challenge 1: The current problem Dental caries is one of the teeth and mouth diseases that is often found in school-age children which is very disturbing to the health of their teeth. The behavior of not maintaining dental hygiene can lead to pathological conditions in the oral cavity. These problems need special handling and preventive measures so that they don't experience toothaches. Challenge 2: What are the efforts for them to have healthy living practices The reading source explains that they only get education from health center personnel, and it is held within a year. Challenge 3: What are the little things that can help children free from dental caries? Conducting counseling for elementary students about the dangers of dental caries if left unchecked. Home care or preventive measures that children can take at home, such as brushing their teeth regularly and limiting eating cariogenic foods, these home care measures can be given in advance through the counseling process and monitoring is carried out every week. Challenge 4: Community groups that can be involved Public health centers, cadres or students who participate in community service activities can be involved in conducting outreach activities, preventive action to target groups Challenge 5: How can your breakthrough be embedded in an existing A program that has been implemented is carrying out activities counseling in schools, the program is already running but requires other programs, namely preventive action (scaling and fissure sealants), implementation of activities, namely making observations first, then students who are at risk of dental caries are carried out by fissure sealant action and a free scaling program for students with low economics. Challenge 6: News links and social media related to news regarding outreach activities have indeed been done a lot, but for preventive action it is still quite minimal, it is hoped that this program can improve dental health for school children, followed by monitoring to build children's habits to maintain their dental health.